ALZHEIMER’S DISEASE: A CONSEQUENCE OF IMPAIRED MITOPHAGY? - SHARMA, VIVEK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Neurodegenerative disorders involve complexities of the pathologies, characterized by the progressive loss of neuronal viability, leading to severe physical and cognitive impairments in affected patients. These disorders although may differ in clinical outcomes yet they share common features such as aggregation of neurotoxic metabolites and perturbed cellular and neuronal homeostasis. Mitochondrion is an indispensable organelle for neuronal survival, and its role and place have become critical in research arena of aging and neurodegenaration. The accumulation of damaged mitochondria has been linked to normal aging and multiple age-related disorders including Alzheimer’s disease (AD). Survival and proper function of mitochondria depend on several attributes that include mitochondrial biogenesis and fusion and fission. Mitophagy is an utmost requirement for degradation and removal of damaged mitochondria where the target mitochondria are identified by the autophagosomes and delivered to the lysosome for degradation. Mitophagy plays important roles in mitochondrial homeostasis, neuroprotection, and resistance to neurodegeneration. AD besides other characteristic features involves mitochondrial dysfunctional, bioenergetic deficit, and altered mitophagy. The autophagy/lysosome pathway that removes damaged mitochondria (mitophagy) is compromised in AD, resulting in the accumulation of dysfunctional mitochondria that contribute to synaptic dysfunction and cognitive deficits by triggering Aβ and Tau accumulation through increases in oxidative damage and cellular energy deficits. The present work reviews the various implications of mitophagy in relevance to the pathology of AD.